2016
DOI: 10.1017/s0029665116000227
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, circadian rhythm and body weight: parallel developments

Abstract: Circadian alignment is crucial for body-weight management, and for metabolic health. In this context, circadian alignment consists of alignment of sleep, meal patterns and physical activity. During puberty a significant reduction in sleep duration occurs, and pubertal status is inversely associated with sleep duration. A consistent inverse association between habitual sleep duration and body-weight development occurs, independent of possible confounders. Research on misalignment reveals that circadian misalign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 120 publications
(217 reference statements)
0
30
0
1
Order By: Relevance
“…As a consequence of involuntarily shifting between two 'time zones': one determined by our internal clock, the circadian rhythm, and the other governed by study, work or other social duties in modern societies, misalignment of biological and social time is almost universal 39 . Disturbance to the circadian clock can not only affect the academic performance of children 40 , but also cause several health problems [41][42][43] . In terms of the visual system, a number of animal studies have demonstrated the importance of regular rhythmicity of lighting conditions on normal ocular growth and emmetropisation 13,14,44 .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of involuntarily shifting between two 'time zones': one determined by our internal clock, the circadian rhythm, and the other governed by study, work or other social duties in modern societies, misalignment of biological and social time is almost universal 39 . Disturbance to the circadian clock can not only affect the academic performance of children 40 , but also cause several health problems [41][42][43] . In terms of the visual system, a number of animal studies have demonstrated the importance of regular rhythmicity of lighting conditions on normal ocular growth and emmetropisation 13,14,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest that increased non-screen sedentary behaviours and inadequate sleep duration are associated with higher night-time cortisol output. With sleep loss, cortisol may exert its deleterious metabolic effects by maintaining high night-time concentrations, which are associated with insulin resistance (IR), suppressed immunity and increased inflammation [44]. Thus, the findings of this integrated approach indicate that the relative distribution of time spent in different physical activities within a 24-h period is important for health promotion and maintenance of diurnal cortisol rhythm in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Robust epidemiological evidence supports the potential role of inadequate sleep as contributing to the current high prevalence of obesity, more specifically abdominal adiposity, in both children and adults (Table ) . There are longitudinal observations suggesting that sleep and body weight develop at least partly in parallel , so causality cannot be extrapolated from these cross‐sectional observations. However, several experimental studies confirm the link between sleep and obesity (Table ).…”
Section: The Influence Of Stress On Sleep Patterns and Quality: Linksmentioning
confidence: 99%